Pengaruh Model Pembelajaran Inquiri Terbimbing Berbasis Lingkungan Terhadap Keterampilan Berpikir Kreatif dan Penguasaan Konsep Ipa Kelas V SD Gugus VIII Kecamatan Abang - Ni Nyoman Lisna Handyani (Purwadita : Jurnal Agama dan Budaya, 2019)
This research aimed to determine differences in the creative thinking skills and mastery science concepts between students learning guide inquiry model and those learning direct instruction. This research is a design experiment with pretest - posttest control group design . The population of this research were all student of class V elementary school cluster VIII Abang District. Samples were taken by means of random sampling. Creative thinking skills and mastery science concepts data measured using tests. The data were analyzed with Manova. Based on the results of hypothesis testing can be made several conclusions: 1) There was a difference in creative thinking skills and mastery science concepts between students who studied with guide inquiry model with students learning with direct instructional model; 2 ) There was a difference in creative thinking skills between students who learned with guide inquiry model with students learning with direct instructional model; 3 ) There were differences between the mastery science concepts of students with learning model guide inquiry and those by direct instructional model.